Exploration of semen quality analyzed by casa-mot systems of brahman bulls infected with BLV and BHV-1 - Pichardo Matamoros, Derling José (2023)
Enzootic bovine leukosis virus (BLV) and bovine herpesvirus 1 (BHV-1) are very important infectious agents for the livestock industry worldwide. The present study aimed to explore the association between natural exposure to BLV and BHV-1 with sperm quality analyzed by Computer-Assisted Semen Analysis (CASA) systems. Ten sexually mature Brahman bulls, with sanitary status BLV+/BHV-1+ (n = 2), BLV−/BHV-1+ (n = 6) and BLV-/BHV-1- (n = 2) were evaluated twice, 30 days apart. Results showed that sanitary status of each bull was not associated with semen quality. It was found that the quality of the semen from the second collection was better due to the interruption of sexual rest. The evidence thus revealed that a bull infected with BLV generated good-quality contaminated semen and, therefore, that it is essential to detect contaminated seminal samples to prevent the spread of BLV. A multivariate analysis showed the presence of four sperm subpopulations in Brahman bulls that differ significantly in their kinematic patterns and with respect to sanitary status (P < 0.05), indicating that infection-free and seronegative bulls present the best kinematic parameters, which improved discrimination of sperm quality according to sanitary status. Overall, the analyses indicate that the seropositive-infected bulls with BLV and BHV-1 should be excluded from beef cattle farms.